Histogenesis of human fetal liver with special histochemical and selective immunohistochemical stains - A Anbarasan; Suvradeep Mitra; Arundhati Kar; Manisha Rajanand Gaikwad; Sweta Singh; Prabhas Ranjan Tripathy (Wolters Kluwer Medknow Publications, 2022)
Introduction: The fetal liver cells can differentiate into both hepatocytes and cholangiocytes based on the induction due to clonogenic properties with high growth potential. Understanding liver histogenesis might be helpful in liver and hepatocyte transplantation. Special histochemical and immunohistochemical stains provide better insight into the hepatic cellular architecture, although the literature regarding the same is relatively sparse. Methodology: This study's objective was to document the microscopic structure of the organization of hepatocytes, the appearance of central veins and sinusoids, the formation of the portal triad, and hematopoietic blasts of the liver at various weeks of gestation by using special histochemical and immunohistochemical stains and also to compare our observations with other regions of India and Western countries. Results: It was observed that the central vein and the arrangement of hepatocytes appeared at 14 weeks of gestation. The sinusoids and portal triads were formed at 15 weeks of gestation. The hemopoiesis level in the liver gradually increased from the 14th to 26th week of gestation, after which it decreased. Conclusion: A better understanding of human fetal liver histogenesis will help future research activities in liver transplantation and hepatocyte transplantation from the aborted/stillborn fetal liver from various weeks of gestation.